Social Responsible Investments in Trinidad and Tobago’s Financial Sector: An examination of the barriers and feasibility of introducing SRI into Banks - Rouff, Malika Adanna (2015)
Economic Nobel Prize winner Paul Krugman during the first wave of the Global economic crisis in 2008 makes the statement - “The people who assured us that markets work; that the private pursuit of profit always leads to a good result have been massively wrong.”(Hurdle, 2008). The global economic crisis would have drastic impacts. It would cause large financial institutions to collapse while governments in the wealthiest nations in the world bail out financial systems. As such it is within this context that SRI takes front stage as a risk mitigating strategy and as a pathway to sustainability. SRI places ESG factors at the forefront of investment decisions thereby creating an avenue for the financial sector to positively impact on economic and social development.